Performance and endocrine responses to differing ratios of concurrent strength and endurance training - Jones, T. W.; Howatson, G.; Russell, M.; French, D. N. (The Journal of Strength and Conditioning Research, 2016)
The present study examined functional strength and endocrine responses to varying ratios of strength and endurance training in a concurrent training regimen. Thirty resistance trained men completed 6 weeks of 3 d·wk-1 of (a) strength training (ST), (b) concurrent strength and endurance training ratio 3:1 (CT3), (c) concurrent strength and endurance training ratio 1:1 (CT1), or (d) no training (CON). Strength training was conducted using whole-body multijoint exercises, whereas endurance training consisted of treadmill running. Assessments of maximal strength, lower-body power, and endocrine factors were conducted pretraining and after 3 and 6 weeks. After the intervention, ST and CT3 elicited similar increases in lower-body strength; furthermore, ST resulted in greater increases than CT1 and CON (all p = 0.05). All training conditions resulted in similar increases in upper-body strength after training. The ST group observed greater increases in lower-body power than all other conditions (all p = 0.05). After the final training session, CT1 elicited greater increases in cortisol than ST (p = 0.008). When implemented as part of a concurrent training regimen, higher volumes of endurance training result in the inhibition of lower-body strength, whereas low volumes do not. Lower-body power was attenuated by high and low frequencies of endurance training. Higher frequencies of endurance training resulted in increased cortisol responses to training. These data suggest that if strength development is the primary focus of a training intervention, frequency of endurance training should remain low.